8(5+h+2)
= 8 * (5 + h + 2)
= 8 * (h + 5 + 2)
= 8 * h + 8 * 5 + 8 * 2
= 8h + 40 + 16
= 8h + 56
Therefore, 8(5+h+2) is equivalent to 8⋅h+56.
Complete the following stepped-out solution to show that 8(5+h+2) is equivalent to 8⋅h+56 . (2 points)
8(5+h+2)
8(h+ +2) Apply the Commutative Property of Addition and add.
8(h+ )
8⋅h+8⋅
Apply the Distributive Property and multiply.
8⋅h+56
5 answers
tha's not the answer
Apologies for the error. Let's correct it:
8(5+h+2)
= 8 * (5 + h + 2)
= 8 * (h + 5 + 2)
= 8 * (h + 7)
= 8h + 8 * 7
= 8h + 56
Therefore, 8(5+h+2) is equivalent to 8h + 56.
8(5+h+2)
= 8 * (5 + h + 2)
= 8 * (h + 5 + 2)
= 8 * (h + 7)
= 8h + 8 * 7
= 8h + 56
Therefore, 8(5+h+2) is equivalent to 8h + 56.
I asked the same question and he gave me the same answer as you
same